Implementasi Sistem Pendukung Keputusan Berbasis MOORA untuk Pemilihan Domba Qurban Terbaik Berdasarkan Kesesuaian dengan Prinsip Syariah - Prabu Aji Malela; A Sidiq Purnomo (Journal of Information System Research (JOSH), 2025)
The selection of sacrificial lambs that comply with Islamic law is an important aspect in the implementation of the Eid al-Adha worship. At Prabu Star Farm, the selection process is still done manually and subjectively, potentially resulting in less accurate decisions. This research aims to develop a web-based Decision Support System (SPK) with the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method to support the selection process objectively and measurably. The system evaluates five main criteria, namely weight, age, health, price, and horn ownership. The MOORA method process includes the formation of a decision matrix, data normalization, weighting based on the type of criteria (benefit or cost), and calculation of the optimization value (Yi) to determine the ranking. Test results on ten alternatives showed that D8 sheep ranked highest (Yi = 0.3021), followed by D1 and D6. The recommendation of D8 was supported by a combination of superior attributes: ideal weight (45 kg), sharia-compliant age (≥ 2 years), healthy condition, rational price, and horn ownership that matched buyer preferences. The system showed high consistency with the manual assessment, and was able to increase efficiency and transparency in the selection process. Thus, the MOORA method is effectively applied in multicriteria decision making for the selection of Sharia-compliant qurban animals.